A review on Contingency Analysis methods of Electrical Power System - Mr.Harisha K, Ms.Sonaxi B Raikar (International Journal of Advanced Science and Technology, 2020)
Component failure in a power system is called contingency. The system should return to acceptable equilibrium state after contingency. Post contingency corrective factors are important to maintain reliability. The corrective factors necessitate the analysis of contingencies. Number of methods is used to perform the contingency analysis. In this review paper the different methods of contingency analysis like transient thermal behaviour method, centrality measures method, a mixed integer programming  model method, real time contingency analysis  with transmission switch method, global power flow method, sensitivity factors method, fast decoupled method and cloud modeling method  has been explored. Their effectiveness in analysing the contingencies and comparison have been made.